The management of seborrheic dermatitis 2020 - Widaty, Sandra; Bramono, Kusmarinah; Listiawan, Muhammad Yulianto; Yosi, Ariyati; Miranda, Eliza; Rahmayunita, Githa; Brahmanti, Herwinda; Lim, Henry W (UI Scholars Hub, 2020)
Background: Seborrheic dermatitis (SD) is a chronic relapsing dermatitis manifesting in the seborrheic area, affecting infants or adults. In Indonesia, the prevalence of SD is 0.99–5.8% of all dermatology cases from 2013 to 2015. SD has been known to be a prominent manifestation among HIV patients, but there is an increasing trend in the general population. Therefore, in 2017, the Indonesian Society for Dermatology and Venereology proposed a consensus for the management of SD in Indonesia based on the discussion from 12 dermatological centers. Concurrent with the development of new drugs, this study aims to evaluate and develop a guideline for the treatment of seborrheic dermatitis in Indonesia to update the previous guidelines in 2017. Methods: Systematic review was based on evidence-based methods, and scientific evidences were acquired through systematic search. Evidence analysis was in accordance with the level of evidence. The available evidences were evaluated, and conclusion was based on the grade of recommendation. Critical appraisal was conducted by experts in dermatology and venereology. Results: Severity of SD can be determined by using the Seborrheic Dermatitis Area Severity Index. The principle of scalp SD management is controlling the scalp condition in a cost-effective manner to make patients comfortable. The recommendations for treatment of adult SD are topical agents, such as antifungals, nonsteroidal anti-inflammatory agents with antifungal properties, corticosteroids, and calcineurin inhibitors. Conclusion: We have updated and added newer agents for the treatment of SD. The approach is divided into scalp or nonscalp and also adult or infantile SD.